2017
DOI: 10.1371/journal.pone.0169743
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inhibition of the Renin-Angiotensin System and Neprilysin Positively Influences Complex Mitochondrial Adaptations in Progressive Experimental Heart Failure

Abstract: BackgroundInhibitors of the renin angiotensin system and neprilysin (RAS-/NEP-inhibitors) proved to be extraordinarily beneficial in systolic heart failure. Furthermore, compelling evidence exists that impaired mitochondrial pathways are causatively involved in progressive left ventricular (LV) dysfunction. Consequently, we aimed to assess whether RAS-/NEP-inhibition can attenuate mitochondrial adaptations in experimental heart failure (HF).Methods and ResultsBy progressive right ventricular pacing, distinct H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Starting from the sequence information of one of these internal peptides, belonging to the MRPL49 protein, we identified neprilysin as a candidate protease activated by altered DA homeostasis. Here, we demonstrated for the first time that the human neprilysin peptidase is enriched in mitochondrial subcellular fractions, an evidence that has already been proposed for orthologues in other species (Wilson et al, 2014; Grois et al, 2017) but that was not confirmed to date in human cells. We also demonstrated that the alteration of DA homeostasis, which is among the earliest events in PD pathogenesis, does not seem to be able to alter the levels of expression of neprilysin, whose activity seems instead to be influenced (increased) in our cellular model.…”
Section: Discussionsupporting
confidence: 63%
“…Starting from the sequence information of one of these internal peptides, belonging to the MRPL49 protein, we identified neprilysin as a candidate protease activated by altered DA homeostasis. Here, we demonstrated for the first time that the human neprilysin peptidase is enriched in mitochondrial subcellular fractions, an evidence that has already been proposed for orthologues in other species (Wilson et al, 2014; Grois et al, 2017) but that was not confirmed to date in human cells. We also demonstrated that the alteration of DA homeostasis, which is among the earliest events in PD pathogenesis, does not seem to be able to alter the levels of expression of neprilysin, whose activity seems instead to be influenced (increased) in our cellular model.…”
Section: Discussionsupporting
confidence: 63%
“…The present work represents the first neprilysin structures from a rabbit source, with rabbit having been used as an important model for studying the role of neprilysin in various disease states (Ichiki et al, 2013;Birner et al, 2012;Grois et al, 2017). The rabbit neprilysin sequence is highly similar to that of human neprilysin, with 94% identity and 97% similarity using standard BLAST parameters (Madden, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we set out to evaluate, whether the tachypacing-heart failure model[9,10] entails progressive myopathy. As a very early, generalized myopathy similar to humans could be established, the enzymatic set-up was characterised by a multi-omics approach, applying pathway-focused gene expression analysis[11] and proteomic methods[12,13]. Pathway analyses gave hints for a failing link between natriuretic peptide signalling and peroxisome-proliferator-activated-receptor-γ-coactivator-1-α (PGC-1α), in line with previous in-vitro and in-vivo data under physiologic conditions[14].…”
Section: Introductionmentioning
confidence: 99%